Quantity discrimination in 9 ungulate species: Individuals take item number and size into account to discriminate quantities - Schaffer, Alina; Caicoya, Alvaro L.; Widdig, Anja; Holland, Ruben; Amici, Federica (Cognition, 2025)
The ability to discriminate quantities is crucial for humans and other animals, by allowing individuals to maximize food intake and successfully navigate in their social environment. Here, we used a comprehensive approach to compare quantity discrimination abilities (i.e. ability to compare sets with different quantities of identical items, reliance on item size and spatial distribution, existence of irrational biases) in 9 different species of ungulates and provide novel insight into the socio-ecological conditions that might favor their emergence. We tested a total of 37 captive subjects including goats (Capra aegagrus hircus), llamas (Lama glama), guanacos (Lama guanicoe), Grevy's zebras (Equus grevyi), Chapman's zebras (Equus burchelli chapmanni), rhinos (Diceros bicornis michaeli), giraffes (Giraffa camelopardalis rothschildi), bison (Bison bonasus) and buffalos (Syncerus caffer nanus). Our results revealed that subjects were able to discriminate quantities when presented with two sets of food items that could differ in number, size and partially density. When presented with sets containing a different number of identical food items, subjects successfully selected the set with more items, with performance overall decreasing when sets had higher ratios (e.g., 1:3 vs 1:5). In addition, subjects could successfully maximize their food intake when both sets had the same number of items, but items had different sizes. However, performance decreased at chance levels when varying both the number of items and their size or distribution. Giraffes performed better than other species in most conditions, and we found no evidence for an irrational bias toward sets with more, smaller items or denser distributions. Overall, our study provides a first comparative assessment of quantity discrimination skills in several ungulate species.